Analisis Potensi Pengelolaan Sampah Domestik Skala Mikro di Kecamatan Johar Baru, Jakarta Pusat - Widyarsana, I Made Wahyu; Ningrat, Boy Cakra; Dewi, Ninne Sevtiana (Universitas Tanjungpura, 2026)
Waste management in the Johar Baru District of Central Jakarta faces significant challenges related to infrastructure, public awareness, and resource constraints. This study aims to analyze the generation, composition, and characteristics of domestic waste, and to evaluate the effectiveness of the implemented waste management policies. The methodology includes a quantitative analysis of waste samples collected over eight consecutive days and laboratory analysis to determine waste characteristics. The results indicate that food waste dominates the waste composition (50.6%), followed by paper and plastic. The waste characteristics in the Johar Baru District show an average moisture content of 65.28% and an average ash content of 89.29%. Waste management policies, such as establishing waste banks and using small vehicles for waste collection, have shown positive results, although their implementation remains limited. Potential waste management initiatives include composting, vermicomposting, Black Soldier Fly (BSF) technology, and plastic recycling. To improve management effectiveness, a more intensive approach to education and increasing public participation is necessary.